Notes on the Text of Maximianus - Welsh, Jarrett T. (Exemplaria Classica, 2012)
This article presents notes on fourteen pas¬sages in the elegiac verses of Maximianus. Its purpose is to suggest some conjectures that may improve the text or, less defini¬tively, that may lead to renewed scrutiny of it.